Analisis Faktor-Faktor Perilaku Konsumen Terhadap Minat Beli Apartemen Grand Sentraland Karawang - A, Aisah; Mulyadi, Dedi; S, Sungkono (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to analyze consumer behavior factors that influence buying interest in Grand Sentraland Karawang apartments. This method uses a qualitative approach, research conducted to understand the phenomena that occur in society when buying apartments. Data collected involved in-depth interviews with a number of apartment employees. It is hoped that the findings of this research will provide deeper insight into consumer preferences and motivations in choosing apartment properties in Karawang, as well as provide strategic recommendations for developers to increase consumer buying interest.